Raising Nursery of Acacia nilotica Var. Cupressiformis with Saline Water - Tomar, O. S.; Kumar, R. M.; Gupta, Raj K.; Minhas, P. S. (Indian Forester, 1997)
High salt concentrations in ground waters pose problems for raising nurseries of tree species under arid climates. Nursery bags should, therefore, be planted and maintained in a manner that either allows irrigation water to move the salts past these bags or reduce the salinity damage. Therefore, an experiments was conducted with Acacia nilotica as test tree where treatments consisted of combinations of (a) salinities of irrigation water (0.4, 2, 4, 6, 8, 10, and 12 dS.m-1), (b) irrigation interval (2, 4 and 6 days) and (c) ratio of depth of irrigation water to cumulative pan evaporation (Diw/ CPE = 0.85, 1.00, 1.15 and 1.30) to achieve varying leaching fractions. The results did not show any potential benefits of maintaining high leaching fractions whereps decreasing irrigation interval to 2 days was observed to reduce salinity damages to some extent. A nilotica was observed to be more tolerant to salinity at germination than early seedling stage. With an Ect of 5.0 dS.m-1 and slope of 19.5 % at seedling stage, this should be rated as moderately tolerant to salinity.